The Genomic Organization of the LILR Region Remained Largely Conserved Throughout Primate Evolution: Implications for Health And Disease - Storm, Lisanne; Bruijnesteijn, Jesse; de Groot, Natasja G.; Bontrop, Ronald E. (Frontiers in Immunology, 2021)
The genes of the leukocyte immunoglobulin-like receptor (LILR) family map to the leukocyte receptor complex (LRC) on chromosome 19, and consist of both activating and inhibiting entities. These receptors are often involved in regulating immune responses, and are considered to play a role in health and disease. The human LILR region and evolutionary equivalents in some rodent and bird species have been thoroughly characterized. In non-human primates, the LILR region is annotated, but a thorough comparison between humans and non-human primates has not yet been documented. Therefore, it was decided to undertake a comprehensive comparison of the human and non-human primate LILR region at the genomic level. During primate evolution the organization of the LILR region remained largely conserved. One major exception, however, is provided by the common marmoset, a New World monkey species, which seems to feature a substantial contraction of the number of LILR genes in both the centromeric and the telomeric region. Furthermore, genomic analysis revealed that the killer-cell immunoglobulin-like receptor gene KIR3DX1, which maps in the LILR region, features one copy in humans and great ape species. A second copy, which might have been introduced by a duplication event, was observed in the lesser apes, and in Old and New World monkey species. The highly conserved gene organization allowed us to standardize the LILR gene nomenclature for non-human primate species, and implies that most of the receptors encoded by these genes likely fulfill highly preserved functions.